2020
DOI: 10.1126/sciadv.aaz8181
|View full text |Cite
|
Sign up to set email alerts
|

[NiFe], [FeFe], and [Fe] hydrogenase models from isomers

Abstract: The study of hydrogenase enzymes (H2ases) is necessary because of their importance to a future hydrogen energy economy. These enzymes come in three distinct classes: [NiFe] H2ases, which have a propensity toward H2 oxidation; [FeFe] H2ases, which have a propensity toward H2 evolution; and [Fe] H2ases, which catalyze H− transfer. Modeling these enzymes has so far treated them as different species, which is understandable given the different cores and ligand sets of the natural molecules. Here, we demonstrate, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“… 29 Our previous study has shown that the BP86 functional behaves well in this NiFe complex. 19 The diamagnetic properties of these ground states predicted by BP86 functional were consistent with 1 H nuclear magnetic resonance spectra and the electron spin resonance. Further, the BP86 has also been used to study the mechanism of catalysis of NiFe hydrogenase, with reliable performance.…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“… 29 Our previous study has shown that the BP86 functional behaves well in this NiFe complex. 19 The diamagnetic properties of these ground states predicted by BP86 functional were consistent with 1 H nuclear magnetic resonance spectra and the electron spin resonance. Further, the BP86 has also been used to study the mechanism of catalysis of NiFe hydrogenase, with reliable performance.…”
Section: Methodssupporting
confidence: 72%
“…The recently developed synthetic model for the catalytic centre of NiFe hydrogenase, [Ni II (X)Fe II (Cl)(CO)(L)](X = N , N ′-diethyl-3,7-diazononane-1,9-dithiolate, L = 1,2,-bis(diphenylphosphino)ethane) (1, Fig. 1 ), reversely catalyses heterolytic H 2 activation in aqueous solution 19 ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…275 A more recent study made use of several techniques including Mössbauer spectroscopy and DFT calculations to set-up structure-property relationships and to show how that the reactivity of all HG enzymes could be mimicked using isomers of a [NiFe] bio-inspired model. 276 With the recent development of dedicated quantum chemistry program packages [277][278][279][280] the use of theoretical spectroscopy has been democratized with the aim to connect the results of computations to experimental observables since spectroscopic properties remain a precise and sensitive fingerprint of the electronic structure for a given system. Consequently, combining spectroscopic characterizations with theoretical calculations has been successfully employed by many research groups to identify the geometric and electronic structures of biomimetic 40,60,265,268,[281][282][283] and bio-inspired [284][285][286][287][288][289][290] models of hydrogenases and appears as a prerequisite to any further computational investigation of their reactivity towards H 2 evolution.…”
Section: Spectroscopic Propertiesmentioning
confidence: 99%
“…These enzymes are of great interest for various environmentally friendly applications such as biofuel cells and (bio)hydrogen production (Lauterbach & Lenz, 2019;Mazurenko et al, 2017;Khetkorn et al, 2017). Numerous chemically synthesized complexes that mimic the function of hydrogenases have also been developed (Ogo et al, 2017(Ogo et al, , 2020Schilter et al, 2016;Ogo, 2017;Dutta et al, 2015;Caserta et al, 2015). Hydrogenases can be divided into three classes according to the metal components of the active site: [NiFe]-hydrogenases, [FeFe]-hydrogenases and [Fe]-hydrogenases (Higuchi et al, 1997;Volbeda et al, 1995;Peters et al, 1998;Shima et al, 2008;Yagi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%